The month of walking alone and BDNF level differ between drug-naive first-episode schizophrenia patients and healthy controls - Zhang, Zhenmei; Fan, Lejia; Yuan, Liu; Li, Zongchang; Ouyang, Lijun; Ma, Xiaoqian; Yang, Zihao; Lv, Jingyan; Chen, Shuting; Chen, Xiaogang; He, Ying (Frontiers in Molecular Neuroscience, 2023)
Schizophrenia is a neurodevelopmental disorder, characterized by impairment in reasoning, affectivity, and social relationships. Previous studies have shown delayed motor development and Brain-Derived Neurotrophic Factor (BDNF) level change in schizophrenia. We researched the month of walking alone (MWA) and BDNF level between drug-naive first-episode schizophrenia patients (FEP) and healthy control (HCs), as well as how they behave in neurocognitive function and severity of symptoms. We find that FEP showed a walking delay and lower BDNF levels compared to HCs, which were associated with cognitive impairment and severity of symptoms. According to the difference and correlation analysis results, and combined with the appropriate application conditions for binary logistic regression, Wechsler Intelligence Scale Picture completion, Hopkins Verbal Learning Test-Revised, and Trail Making Test: part A were added to the binary logistic regression analysis to distinguish FEP and HCs. Our study may extend insight into the early identification of patients with schizophrenia versus healthy populations.